2020
DOI: 10.3389/fimmu.2020.596772
|View full text |Cite
|
Sign up to set email alerts
|

IL-2-Agonist-Induced IFN-γ Exacerbates Systemic Anaphylaxis in Food Allergen-Sensitized Mice

Abstract: Food allergies are common, costly and potentially life-threatening disorders. They are driven by Th2, but inhibited by Th1 reactions. There is also evidence indicating that IL-2 agonist treatment inhibits allergic sensitization through expansion of regulatory T cells. Here, we tested the impact of an IL-2 agonist in a novel model for food allergy to hen´s egg in mice sensitized without artificial adjuvants. Prophylactic IL-2 agonist treatment expanded Treg populations and inhibited allergen-specific sensitizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 73 publications
1
8
0
Order By: Relevance
“…IL-2 and IFN-γ support Th1 cell proliferation and antagonize the effects of IL-4 and TNF-α. 25 All this conforms with the findings of this study: the Tα1 group had lower sputum supernatant levels of IL-4 and TNF-α but higher sputum supernatant levels of IL-2 and IFN-γ compared with the control group. Previous studies have also shown that Tα1 can reduce liver inflammation and reduce hepatocyte apoptosis by down-regulating TNF-α and up-regulating IL-10.…”
Section: Discussionsupporting
confidence: 91%
“…IL-2 and IFN-γ support Th1 cell proliferation and antagonize the effects of IL-4 and TNF-α. 25 All this conforms with the findings of this study: the Tα1 group had lower sputum supernatant levels of IL-4 and TNF-α but higher sputum supernatant levels of IL-2 and IFN-γ compared with the control group. Previous studies have also shown that Tα1 can reduce liver inflammation and reduce hepatocyte apoptosis by down-regulating TNF-α and up-regulating IL-10.…”
Section: Discussionsupporting
confidence: 91%
“…In the control group we observed an elevation in both IFNγ and IL-10, which is typically associated with the suppression of Th2 responses. Here we hypothesize that IFNγ may be acting as an enhancer of mast cell degranulation 56 and IL-10 may be proinflammatory under certain conditions, as it was shown to play a critical role in the development of Th2 responses in an allergic dermatitis mouse model. 57 …”
Section: Discussionmentioning
confidence: 99%
“…In the control group we observed an elevation in both IFNg and IL-10, which is typically associated with the suppression of Th2 re-sponses. Here we hypothesize that IFNg may be acting as an enhancer of mast cell degranulation 56 and IL-10 may be proinflammatory under certain conditions, as it was shown to play a critical role in the development of Th2 responses in an allergic dermatitis mouse model. 57 Immune tolerance in the context of hepatic AAV gene delivery is predicated on a number of variables including, but not limited to, the AAV capsid, promoter, and transgene product expression levels.…”
Section: Discussionmentioning
confidence: 99%
“…Hyperinflammation and cytokine storm syndrome (CSS) are among the major causes of acute respiratory distress syndrome (ARDS), multiorgan failure, and death due to severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection [ 13 15 ]. An unexpected increase in the circulating levels of proinflammatory cytokines, especially interleukin-1 (IL-1), IL-6, gamma interferon (IFN γ ) and tumor necrosis factor- α (TNF- α ), leads to hyperinflammation and the CSS [ 16 ]. When CSS occurs, different immune cells ( e.g., neutrophils, macrophages, and T cells) infiltrate into the site of infection, and consequently, a cascade of damage of the vascular barrier, diffuse alveolar damage and lung injury, multiorgan failure, and ultimately death occurs [ 17 ].…”
Section: Covid-19 and The Cytokine Storm Syndromementioning
confidence: 99%
“…When CSS occurs, different immune cells ( e.g., neutrophils, macrophages, and T cells) infiltrate into the site of infection, and consequently, a cascade of damage of the vascular barrier, diffuse alveolar damage and lung injury, multiorgan failure, and ultimately death occurs [ 17 ]. ARDS is one of the major consequences of CSS that directly link to severe sequel and mortality in acute COVID-19 patients [ 13 , 16 ]. Therefore, therapeutic strategies to mitigate the risk of CSS and ARDS are essential.…”
Section: Covid-19 and The Cytokine Storm Syndromementioning
confidence: 99%